COMPARATIVE STUDY OF THE STANDARD OVEN-DRYING AND THE SPEEDY METHOD FOR DETERMINING SOIL WATER CONTENT - Ribeiro, K. M.; Castro, M. H. de C.; Ribeiro, K. D.; Lima, P. L. T.; Abreu, L. H. P.; Barros, K. L. C. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Soil moisture determines the water content retained in the soil porous spaces. Knowledge of this property is essential, as water interfere on soil behavior. Among several methods available to evaluate this property, there is the speedy and oven-drying methods. The aim of this research was to compare soil moisture results obtained through the standard oven-drying method and the speedy method. Therefore, four soil class samples (Latossolo Vermelho, Latossolo Vermelho-Amarelo, Cambissolo and Argissolo) were collected in triplicate, from Lavras - MG, Brazil, at Federal University of Lavras - UFLA, and analyzed for particle-size and moisture content. In order to quantify soil moisture, oven-drying method was performed according to NBR 6457 procedures, whereas speedy method was realized according to procedures from National Department of Highways (DNER-ME 052/94). It was verified that the speedy method provided values of soil moisture lower than those determined by the oven-drying method, possibly due to the difficulty of the particles total disintegration inside the apparatus, wherein the soil moisture increase led to higher differences between methodologies. According to the divergences stated between methods, linear regression analyzes were performed to obtain a calibration equation of the speedy method to reach a more approximate value in relation to the oven-drying method. The best fitting model was hSC= 46,292254 – 333,088487 / hSD, with a R² = 0,8843.